Gas chromatography–mass spectrometry analysis of organic pollutants in French soils irrigated with agro-industrial wastewater - Maurin, Nicolas; Sayen, Stéphanie; Guillon, Emmanuel (Frontiers in Environmental Science, 2023)
The use of agro-industrial wastewater in the agricultural sector is an interesting practice to save resources but it can bring various contaminants to the receiving soils. In this study 19 organic pollutants (8 polycyclic aromatic hydrocarbons (PAH), 6 BTEX, 4-tert-octylphenol, 4-octylphenol, 4-n-nonylphenol, tributyltin and diethylphtalate) were analyzed by gas chromatography-mass spectrometry (GC-MS) in soils irrigated with agro-industrial wastewater from sugar refinery. The soils were sampled at five different locations to evaluate the contamination heterogeneity. Microwave-assisted extraction (MAE) was performed using methanol and hexane and extraction yields ranged from 44 to 96%. The detection limits were between 0.2 and 5 ng.g-1 for PAH, 3.1 ng.g-1 for diethylphthalate, 2.5 ng(Sn).g-1 for tributyltin and until 69 ng.g-1 for phenol compounds. The highest contaminant concentrations measured in the soil samples, between 0.4 ng.g-1 and 1.2 ng.g-1, were monitored for PAH molecules, including napthalene, anthracene, fluoranthene, indeno(1,2,3-c,d)pyrene, benzo[a]pyrene, benzo[b]fluoranthene, benzo[k]fluoranthene, and benzo[ghi]perylene. Toluene, ethylbenzene, xylene isomers accounted from 21 to 66 ng.g-1 (mostly toluene). Benzene, 4-tert-octylphenol, 4-octylphenol, 4-n-nonylphenol, tributyltin and diethylphtalate were not detected in soils.